Error bounds, metric subregularity and stability in Generalized Nash Equilibrium Problems with nonsmooth payoff functions. (2nd October 2016) - Maréchal, M.; Correa, R.
Abstract : In this paper, we study the calmness of a generalized Nash equilibrium problem (GNEP) with non-differentiable data. The approach consists in obtaining some error bound property for the KKT system associated with the generalized Nash equilibrium problem, and returning to the primal problem thanks to the Slater constraint qualification.